2016
DOI: 10.5116/ijme.5709.2a7e
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived versus objectively measured competence in performing clinical practical procedures by final year medical students

Abstract: ObjectivesTo determine and compare the self-perceived and objectively measured competence in performing 14 core-clinical practical procedures by Final Year Medical Students of the University of Zambia.MethodsThe study included 56 out of 60 graduating University of Zambia Medical Students of the 2012/2013 academic year. Self-perceived competence: students rated their competence on 14 core- clinical practical procedures using a self-administered questionnaire on a 5-point Likert scale. Objective competence: it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…Most students initially selected the right choice for fluid resuscitation (crystalloids), so the scores did not increase significantly. Our findings were similar to a study that reported that the final-year medical students had low self-competence in the intubation procedure 14. However, our scenario or mannequins did not represent real patterns of respiratory failure, so students were reluctant to intubate.…”
Section: Discussionsupporting
confidence: 87%
“…Most students initially selected the right choice for fluid resuscitation (crystalloids), so the scores did not increase significantly. Our findings were similar to a study that reported that the final-year medical students had low self-competence in the intubation procedure 14. However, our scenario or mannequins did not represent real patterns of respiratory failure, so students were reluctant to intubate.…”
Section: Discussionsupporting
confidence: 87%
“…The literature indicates that the correlation between self-perceived competence and objectively assessed performance is either absent or discordant for essential clinical procedures, and it is weak for prescribing skills. 13 , 23 , 24 However, these findings, and the fact that both competencies were among the lowest in perceived competence, should not discourage the assignment of students to these tasks, but raises the need for additional care in training and supervision in this instance.…”
Section: Discussionmentioning
confidence: 97%
“…Our study utilized subjective measures of clinical competency; however, the factors affecting the correlation between self‐perceived and observed competency are still unclear and medical students may over‐report confidence due to fear of revealing areas of weakness . Future studies could further investigate the link between subjective and observed clinical competency.…”
Section: Discussionmentioning
confidence: 99%